Pendampingan Teknis Perencanaan dan Penataan Masjid Al-Khair Sebagai Masjid Ramah Anak dan Disabilitas - Rezi Munizar; Buyung Mantap; M. Wisridani P.; Yoka Mahendra (Journal of Community Service and Engagement, 2026)
This community service activity focuses on technical assistance for the planning and spatial arrangement of Al-Khair Mosque as a child-friendly and disability-inclusive mosque. The program was implemented using a participatory approach involving mosque managers and congregants to ensure relevance and sustainability. Field observations revealed several accessibility and safety limitations related to entrance access, circulation paths, ablution areas, and supporting facilities. Identification of user needs highlighted diverse requirements among children, elderly worshippers, and persons with physical and sensory disabilities. Participatory discussions with mosque administrators served as a platform to integrate empirical findings with local perspectives and management capacities. Based on these processes, inclusive technical recommendations were formulated, emphasizing accessibility, safety, comfort, and gradual implementation. The results demonstrate that participatory technical assistance strengthens managerial awareness, enhances design responsiveness, and supports inclusive religious participation. This program confirms that integrating user-based data, inclusive design principles, and local commitment is essential for transforming mosques into accessible and welcoming worship spaces for all community members